Double-Skin Façade (DSF) Application to Address the Performance Problems of the Contemporary Buildings in Yemen - Al-Awag, Eman; Abd Wahab, Izudinshah; Abass, Fatma (International Journal of Sustainable Construction Engineering and Technology, 2022)
The double-skin façade (DSF) recently received significant attention from specialists and researchers due to its possibility to improve the building’s performance. In Yemen, which has various climates, contemporary buildings suffer from many performance problems due to the weak interaction of their facades with the surrounding environment. Therefore, this paper aims to explore the DSF possibilities in enhancing the contemporary buildings’ performance in Yemen by reviewing previous studies investigating the DSF system and the performance of contemporary Yemen buildings to identify and summarize the solutions and treatments offered by the DSF to improve these buildings’ performance. The analysis revealed that implementing the DSF system can enhance the performance of the contemporary buildings in Yemen in terms of interior comfort and energy-saving when reaching the proper design of this system that appropriately responds to the region’s climate. Yet, there are problems that the DSF may not fully meet, represented by building loads and construction and maintenance costs.